Performance Assessment with Multiple Intelligence Differentiation to Measure Communication Skills: Application of Many Facet Rasch Model - Rahman, Aulia; Liliawati, Winny; Rusdiana, Dadi (FKIP Universitas Lampung, 2023)
Abstract: This research aims to determine the characteristics of the PABMMSB instrument. Comprising seven task types and assessment rubrics measuring communication skills across four indicators. Employing a Mixed Methods Exploratory Sequential: Instrument development model with purposive sampling, the study involved 39 prospective physics teacher students. Data was obtained from 5 types of assignments that were selected and then assessed by seven raters and the result was that IKK01 did not meet the ZStd score criteria with a value of -2.2. However, because the MnSq (0.82) and PtMea (0.59) values have met the criteria, the ZStd value can be ignored and IKK01 is still declared valid, and for IKK02, IKK03, and IKK04 all have met the criteria and all indicators tested have met the criteria and are declared valid to measure communication skills. Apart from that, a reliability value of 0.87 was obtained and was included in the Very Good criteria. Keywords: characteristics, performance assessment, multiple intelligences, communication skills, rasch model, facet. Abstrak: Penelitian ini bertujuan untuk mengetahui karakteristik instrumen PABMMSB. Instrumen yang dikembangkan terdiri dari tujuh jenis tugas dan rubrik penilaian untuk mengukur keterampilan komunikasi dengan empat indikator. Penelitian ini menggunakan Mixed Methods Exploratory Sequential: Instrument development model dengan teknik purposive sampling. Uji coba dilakukan kepada 39 orang mahasiswa calon guru fisika didapatkan data dari 5 jenis tugas yang dipilih kemudian dinilai oleh tujuh orang rater dan didapatkan hasil bahwa IKK01 tidak memenuhi kriteria nilai ZStd dengan nilai -2.2. akan tetapi karena nilai MnSq (0.82) dan PtMea (0.59) sudah memenuhi kriteria maka nilai ZStdnya bisa diabaikan dan IKK01 tetap dinyatakan valid, dan untuk IKK02, IKK03, dan IKK04 semuanya telah memenuhi kriteria dan seluruh indikator yang di ujikan memenuhi kriteria dan dinyatakan valid untuk mengukur keterampilan komunikasi. Selain itu, didapatkan nilai reliabilitas sebesar 0.87 dan termasuk kedalam kriteria Bagus sekali. Kata kunci: karakteristik, penilaian kinerja, kecerdasan majemuk, keterampilan komunikasi, rasch model, facet. DOI: http://dx.doi.org/10.23960/jpmipa/v24i4.pp9232-943